PERBANDINGAN NILAI TAMBAH PRODUK OLAHAN IKAN LELE DI GRIYA ULAM-Q KABUPATEN KEDIRI (Comparison Of Value-Added ProductsProcessed Catfish A Case Study On Shredded Catfish And Catfish Nuggets At Griya Ulam-Q In Kediri District) - PRATAMA, WAHYU ADITYA; FATMAWATI, ERLIN WIDYA; MAHARANI, NAVITA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2024)
The purpose of this research is to determine the process of processing catfish into processed catfish in the form of floss and  nuggets and to find out the comparison of the amount of added value and profits obtained by MSMEs processing catfish in Griya Ulam-Q, Ngasem District, Kediri Regency. This research was conducted in July - August 2023. The data analysis method used was the hayami value added analysis method. The respondents in this research were catfish processing businesses under the auspices of Griya Ulam-Q, Kediri Regency. The research results show the process of processing catfish into floss and  nuggets with various additional raw materials. In calculating the added value using the Hayami method, the added value of abon was IDR 46,822.40 per kilogram, and for nuggets IDR 158,814 per kilogram. Based on the added value calculation using the hayami method, the smallest added value ratio is the added value of floss, namely 31.21%. Meanwhile, the largest added value ratio is the added value of catfish nuggets of 52.94%. The largest level of profit obtained was from floss, namely 88.79%.